2009
DOI: 10.1537/ase.090130
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial thickness is not independent of luteal phase day in a rural Polish population

Abstract: The endometrium is important for luteal phase function, implantation, placentation, and gestation. Endometrial morphology has been shown to impact early pregnancy success in in vitro fertilization and egg donor cycles and has been implicated in conception success in spontaneous cycles. However, few studies have monitored endometrial morphology in normo-ovulatory women or examined possible population variation in its physiology or thickness. Further, the methodology of most studies of the endometrium is to take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…The timing of urine collection in the original study was to measure C‐peptide concentrations (Clancy et al, ), and designed to promote ease of collection for participants, and thus four consecutive early mid follicular days were sampled (days 3–6 from first day of menses), and three consecutive early mid luteal days (days 21–23). In designing this secondary analysis of urine samples for CRP, we hypothesized that these two time periods represented times of low inflammatory activity of reproductive origin, as menses would be nearly over and the implantation window not yet, or only just begun for most participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The timing of urine collection in the original study was to measure C‐peptide concentrations (Clancy et al, ), and designed to promote ease of collection for participants, and thus four consecutive early mid follicular days were sampled (days 3–6 from first day of menses), and three consecutive early mid luteal days (days 21–23). In designing this secondary analysis of urine samples for CRP, we hypothesized that these two time periods represented times of low inflammatory activity of reproductive origin, as menses would be nearly over and the implantation window not yet, or only just begun for most participants.…”
Section: Discussionmentioning
confidence: 99%
“…Younger women are able to recall their age at menarche with much greater accuracy (Koo and Rohan, ; Koprowski et al, ; Must et al, ) than women into middle age (Cooper et al, ). Because age at menarche is later in this sample than industrial population samples (Clancy et al, ), and participants were 20–40 years old, the time of recall was in the range of other studies that have shown good accuracy in recalled age at menarche.…”
Section: Methodsmentioning
confidence: 99%
“…While the causes of variation in human menstrual reabsorption have not been explicitly tested, several studies suggest which factors might control how much blood, and thus iron, a body loses during menstruation and how much it reabsorbs and reuses. For example, some evidence indicates that menstrual blood loss is sensitive to energetic condition (Clancy, ; Clancy et al, ; Rowe et al, ), although this has not yet been tested directly. The Polish population, Clancy et al () studied and the Kenyan population Miller () studied have a high physical workload; the Kenyan women also had poor nutritional status.…”
Section: Iron and Menstruationmentioning
confidence: 99%
“…Women (n = 1326) were recruited at the Mogielica Human Ecology Study Site in the Beskid Wyspowy region of southern Poland between 2003 and 2018. Details about the study site and recruiting procedures have been described elsewhere (Clancy et al, , ; Lee, Rogers, Galbarczyk, Jasienska, & Clancy, ; Puskarczyk et al, ). All women provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Research was conducted in the mountainous Beskid Wyspowy region, where women historically grew up living and/or working on family farms and continuing to work on farms and large vegetable gardens into adulthood (Jasienska, ). Women in this region have later ages at menarche than the United States (Clancy, Ellison, Jasienska, & Bribiescas, ). While farming is still common, the region is transitioning toward a more labor‐based market (Colleran, Jasienska, Nenko, Galbarczyk, & Mace, ).…”
Section: Introductionmentioning
confidence: 99%